Gambaran Peresepan Antibiotik di Apotek K-24 Sampangan Kota Semarang - Ariska Nur Permatasari (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
Antibiotics are used to treat bacterial infections by killing or inhibiting their growth. Improper use can lead to resistance, so proper prescribing is essential for patient safety. This study aims to determine the description of antibiotic prescribing at the K-24 Sampangan Pharmacy, Semarang City. This study is a descriptive observational study with retrospective data from prescription sheets of patients who received antibiotics at the K-24 Sampangan Pharmacy, Semarang City for the period January – April 2024. Data were analyzed qualitatively and quantitatively based on age, gender, dosage form, type of antibiotic, indications for other drugs combined with antibiotic prescriptions, antibiotic class, spectrum and use of single or combination antibiotics. The results showed that the number of prescriptions that met the inclusion criteria was 130 prescriptions. The patients who received the most antibiotic prescriptions were female (55.38%). The age of 0– 5 years received the most antibiotic prescriptions (20.77%). The most commonly used preparation was tablet form (36.92%). The most common type of antibiotic was amoxicillin (29.23%). Other drug indications combined with antibiotics are mostly mucolytic (25.98%). Broad spectrum antibiotics are mostly used (99.23%). The most common single use is amoxicillin (29.23%) and the most common use of combination between amoxicillin and clavulanic acid is 9 (6.92%).